Wykonaj mnożenia, a następnie zredukuj wyrazy podobne.
a) -2(x^3+ 2x² - x )- x (- 2x² + 4)+1/2x (6x+8)
b) 2xy(x-y) - 3x(xy + 1) + 4y(xy-1)
PROSZĘ O SZYBKĄ POMOC Z GÓRY DZIĘKUJĘ ​


Odpowiedź :

a)

[tex] - 2( {x}^{ 3} + {2x}^{2} - x) - x( { - 2x}^{2} + 4) + \frac{1}{2} x(6x + 8) = { - 2x}^{3} - {4x}^{2} + 2x + {2x}^{3} - 4x + {3x}^{2} + 4x = { - x}^{2} + 2x[/tex]

b)

[tex]2xy(x - y) - 3x(xy + 1) + 4y(xy - 1) = {2x}^{2} y - 2x {y}^{2} - {3x}^{2} y - 3x + 4x {y}^{2} - 4y = - {x}^{2} y + 2x {y}^{2} - 3x - 4y[/tex]